Epistemologi Ilmu Dalam Perspektif Filsafat Isyraqi (Suhrawardi al-Maqtul) - Zikri Adib Kurnia; Ahmad Fajar Shodiq; Imron Rossidy (Jurnal Multidisiplin Indonesia, 2024)
Isyraqi or in philosophical language illuminationism is a thought developed by Suhrawardi Al Maqtul by combining the teachings of Sufism and philosophy. Epistemologically, Islamic thought was born as a reaction or alternative to the weaknesses that occurred in previous philosophy, especially Aristotelian paripathetics. There are two main teachings in Isyraqi philosophy, namely gradations of essence and self-awareness. From these two teachings, a third teaching or theory was born, namely the Mythical Realm. The israqi philosophical view regarding methods of gaining knowledge emphasizes the importance of enlightenment or "ishraq" in understanding reality. Therefore, the aim of the research is to explain how the epistemology of science in the view of Islamic philosophy in gaining knowledge. This article was written using a qualitative library research approach, namely by examining reading sources that are relevant to the research in question, as well as library research using previous research findings related to the philosophy of science. The results of this research found that Isyraqi philosophy views science as more than just rational knowledge or empirical knowledge. Knowledge is often associated with divine light or spiritual enlightenment that guides individuals towards a deep understanding of reality. Knowledge is seen as the result of spiritual experience and intuitive insight that exceeds the limits of reason. Knowledge in Isyraqi philosophy helps individuals understand the nature of existence and their relationship to a higher reality and knowledge comes from two main sources: intuition and spiritual experience.